Saxagliptin Attenuates Albuminuria by Inhibiting Podocyte Epithelial- to-Mesenchymal Transition via SDF-1α in Diabetic Nephropathy - Chang, Yun-peng; Sun, Bei; Han, Zhe; Han, Fei; Hu, Shao-lan; Li, Xiao-yu; Xue, Mei; Yang, Yang; Chen, Li; Li, Chun-jun; Chen, Li-ming (Frontiers in Pharmacology, 2017)
Dipeptidyl peptidase-4 (DPP-4) inhibitor saxagliptin has been found to reduce progressive albuminuria, but the exact mechanism is unclear. Podocyte epithelial-to-mesenchymal transition (EMT) has emerged as a potential pathway leading to proteinuria in diabetic nephropathy (DN). Stromal cell–derived factor-1α (SDF-1α), as one of substrates of DPP-4 enzyme, can activate protein kinase A pathway and subsequently inhibit its downstream factor of transforming growth factor-β1 (TGF-β1), which induces the podocyte EMT. Thus, this study was designed to test the hypothesis that saxagliptin could reduce progressive albuminuria through preventing podocyte EMT by inhibiting SDF-1α cleavage in diabetic nephropathy. Through a series of method such as ELISA, Western blot, immunochemistry/immunofluorescence, results showed that saxagliptin treatment obviously ameliorated urinary microalbumin excretions and renal histological changes in high-fat diet/streptozotocin-induced diabetic rats. Furthermore, saxagliptin-treated diabetic rats presented a suppression of DPP-4 activity/protein expression paralleled with restoration of SDF-1α levels, subsequently hindered NOX2 expression and podocyte EMT. In vitro studies, we observed consistent changes that saxagliptin significantly inhibited increased DPP-4 activity/expression, oxidative stress and podocyte EMT. When applying SDF-1α receptor blockade (AMD3100) to the cultured podocytes, we further confirmed the essential role of SDF-1α on podocyte EMT inhibition. Taken together, we elucidated for the first time that saxagliptin treatment played an essential role in ameliorating progressive DN by preventing podocyte EMT through SDF-1α related pathway, suggesting saxagliptin could offer renoprotection and SDF-1α might be a potential therapeutic target of DN.